PENGELOLAAN FOOD WASTE RUMAH TANGGA BERBASIS KOMUNITAS: SEBUAH KAJIAN LITERATUR - Dyah Wahyuning Tyas; Rosalina Nur Annisa; Dodik Prakoso Eko Hery Suwandojo (Bajang Institute, 2025)
Household food waste is a significant contributor to the municipal solid waste problem. Improper management of food waste can cause negative environmental, economic and social impacts. This literature review aims to analyze various studies related to community-based household food waste management, processing methods, and factors that influence the success of its implementation. The results show that community-based household food waste management has great potential in reducing waste volume, producing value-added products, and increasing community participation in sustainable waste management. The successful implementation of this approach is influenced by various factors, including community awareness and participation, government support, and infrastructure availability. Comprehensive and collaborative efforts from various parties are needed to overcome the challenges and develop an effective and sustainable food waste management model.